Answer:
Step-by-step explanation:
log3^(2x+3) = log243
(2x+3)log3 = log243
2x+3 = log243/log3
2x = (log243/log3)-3
x = [(log243/log3)-3]/2
x = (5-3)/2
x = 2/2
x = 1
Check:
3^2(1)+3 = 243
3^2+3 = 243
3^5 = 243
3×3×3×3×3 = 243
9×9×3 = 243
81×3 = 243
243 = 243
Answer:
the third option: x + 2(2x - 4) = 10
Step-by-step explanation:
the question tells you that y = 2x - 4.
so, instead of writing y in the equation, just replace it with 2x - 4.
x - 2y = 10
becomes
x - 2(2x-4) = 10
The answer is c. Because 4.5 * 2 is 9 then you add 0.5 so the answer is 9.5
Answer:
13
Step-by-step explanation:
We need to write our answer in exponential form. Ask yourself the question, "What times itself 3 times will give you 2197?" Your answer is
. This will go inside of your cube root. You now have
. Since there's a power of 3 and a cube root, those cancel each other out, and your answer is 13.